Perception and practice regarding infection control measures in Radiology department during pre-COVID and COVID times—A survey among radiologists and a review of current concepts and literature - Srivastava, Saubhagya; Rai, Santosh PV; Jain, Animesh; Shenoy, Suchithra (Indian Journal of Radiology and Imaging, 2021)
Aim: In this study, we aim to evaluate the perception and practice of IPC measures by Radiologists during pre-COVID and present COVID times, while conducting a thorough review of current concepts and literature, to provide a standard operating procedure (SOP) for radiology operations. Methods: This study was conducted by Department of Radiodiagnosis and Imaging, Kasturba Medical College, MAHE, Mangalore. After obtaining approval from the institutional ethics committee, and other required permissions, the Google form questionnaire was sent to 350 Radiologists via email and text during the period of May 2020. Data was collected by time-based sampling in the period of fifteen days during the end of the total lockdown time. Results: 54% (n = 152) reported never attending a training session on (Infection Prevention & Control) IPC prior to the COVID-19 outbreak. The perception regarding IPC were found to be good among radiologists as majority of the respondents were correctly able to answer questions regarding IPC. 86% (n = 152) of the respondents believed that their knowledge on IPC has improved during the COVID-19 pandemic. However, it was revealed that majority of the respondents only started to practice appropriate contact and droplet / procedural precautions only after the COVID-19 outbreak. Conclusion: The present COVID-19 scenario coupled with the lack of knowledge and training regarding IPC amongst radiologists evident from the results of our survey, highlights the need for proper training and establishing standard operating procedures and best practices in IPC pertinent to modern radiology practice
Keywords: COVID-19; empirical precautions; infection prevention and control; procedural precautions; radiology; source control; standard operating procedure; standard precautions; triage